تقييم نتائج المعالجة الفيزيائية في دوار الوضعة الاشتدادي السليم - الرستم, محمد; ابراهيم, مصطفى; مبارك, إياد (Latakia University Journal -Medical Sciences Series, 2019)
مليون شخص من مراجعي العيادات كل سنة يكون لديهم شكوى اضطراب توازن. ودور اختصاصي أمراض الأنف والأذن والحنجرة هو تشخيص الدوار من منشأ دهليزي. ودوار الوضعة الاشتدادي السليم هو أحد أشيع أسباب الدوار من منشأ دهليزي. والهدف من البحث هو تحديد فعالية العلاج الفيزيائي في دوار الوضعة الاشتدادي السليم بإجراء مناورة إيبلي. تناولت الدراسة مئة وخمسين مريضاً شخّص لديهم دوار الوضعة الاشتدادي السليم أجري لهم علاج فيزيائي ودوائي. وقد تبين أن العلاج الفيزيائي فعال جداً في علاج دوار الوضعة الاشتدادي السليم. A million of patients annually consult their physicians with the complaint of dizziness. The role of the otolaryngologist includes examining the cause of vertigo. Benign Paroxysmal Positional Vertigo is one of the most common Peripheral causes of vertigo. The aim of this study is to determine the activity of physical treatment by "Epley maneuver". The study involved one hundred and fifty persons suffering from BPPV. Those patients were treated with Epley maneuver and medical treatment. The results of physical treatment were very good.